Functional Outcomes of Perilunate Dislocation Injuries Treated With Deep Friction Massage: One Year Follow-Up - Pantouvaki̽ Anna; Velivasakis, George; Kastanis, Grigorios (International Journal of Innovative Research in Medical Science, 2019)
Perilunate injuries are the most complex severe injuries occurring in the wrist and there is a lack of suggested therapeutic protocols in literature, concerning rehabilitation programs. Although Deep friction massage is a widely known technique in the field of tendinopathies, ligamentous injuries and chronic pain management, its therapeutic value has not yet been documented in treatment of wrist lesions. The purpose of this study is to suggest that the technique should be considered as a good therapeutic method with good tolerance in patients and good functional outcomes and should be included in management of perilunate injuries.